Physical and Rheological Studies of Biscuits Developed with Different Replacement Levels of Pumpkin (Cucurbita maxima) Peel, Flesh, and Seed Powders. (21st March 2023) - Hussain, Ashiq; Kausar, Tusneem; Aslam, Jawed; Quddoos, Muhammad Yousaf; Ali, Atif; Kauser, Samina; Zerlasht, Mehwish; Rafique, Ayesha; Noreen, Saima; Iftikhar, Khansa; Waheed Iqbal, Muhammad; Shoaib, Muhammad; et al.
Abstract : Several studies have been found in the literature about the phytochemistry, nutritional profiles, and pharmacological potential of pumpkin and pumpkin-based food products but a very few data have been found about the impact of the addition of pumpkin powders on physical and rheological behaviors of bakery products. The present research work was conducted to investigate that powder of which part of pumpkin and in what percentage could prove the most acceptable to develop good quality biscuits with optimum rheological and physical characteristics, which will be very useful to utilize pumpkin waste streams with effective and efficient mechanism for benefit of mankind in terms of development of new variety of bakery items. Peel, flesh, and seeds of pumpkin were utilized in the form of dried powder at 0, 5, 10, and 15% replacement levels to develop biscuits. Farinographic studies revealed that water absorption and dough development time were significantly increased to 65.69 ± 0.60% and 5.80 ± 0.012 min, respectively, at 15% pumpkin peel powder replacement, whereas dough stability was significantly decreased for 15% replacement level of pumpkin peel, flesh, and seed powders. Mixing tolerance index was significantly increased by these replacements. Mixographic studies revealed that mixing time of control dough was 3.55 ± 0.029 min, which was significantly decreased to 3.03 ± 0.015, 2.94 ± 0.023, and 3.23 ± 0.017 min for 15% replacement level of pumpkin peel, flesh, and seed powders, respectively. Similarly, peak height values were significantly decreased as replacement levels of pumpkin powders were increased up to 15%. Width and spread factor were significantly decreased, whereas thickness was significantly increased by these replacements. These replacements of pumpkin powders with white flour did not pose negative impact on rheological behavior of composite flours, which ultimately resulted in the development of improved quality biscuits.